Proceedings 2007 Conference on Plantation Commodities: Visionary agriculture: Malaysian commodity crops in 100 years, 3-4 July, 2007, Putra World Trade Centre, Kuala Lumpur, Malaysia - Conference on Plantation Commodities (2007 : Kuala Lumpur, Malaysia); Lembaga Koko Malaysia; Malaysia. Kementerian Perladangan dan Komoditi (Sabah : Malaysian Cocoa Board, 2007)
Includes bibliographical references.